1987
DOI: 10.1073/pnas.84.19.6889
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 4 (B-cell stimulatory factor 1) can enhance or antagonize the factor-dependent growth of hemopoietic progenitor cells.

Abstract: Our studies show that although interleukin 4 (IL-4) fails to stimulate significant colony formation by bone marrow progenitor cells, it enhances erythroid, granulocyte, macrophage, and mast-cell colony formation when used as a costimulant with erythropoietin, granulocyte colony-stimulating factor, macrophage colony-stimulating factor, and interleukin 3 (IL-3), respectively. In contrast, IL-4 suppresses IL-3-dependent colony formation by granulocyte and macrophage progenitor cells and by multipotential progenit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
63
0
1

Year Published

1988
1988
1998
1998

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 212 publications
(67 citation statements)
references
References 17 publications
3
63
0
1
Order By: Relevance
“…Indeed, it has been demonstrated that IL-4 suppresses the generation of LAK cells from PBL by IL-2 (42,43). Moreover, IL-4 has been shown to inhibit the factor-dependent growth of pre-B cells from bone marrow precursors (44) . In addition, our finding that IL-4 antagonizes IL-2-dependent growth of activated normal B cells is in line with the recent data obtained with chronic lymphocytic leukemia B cells (B-CLL), whose IL-2-dependent proliferation is totally blocked by IL-4 (45) .…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it has been demonstrated that IL-4 suppresses the generation of LAK cells from PBL by IL-2 (42,43). Moreover, IL-4 has been shown to inhibit the factor-dependent growth of pre-B cells from bone marrow precursors (44) . In addition, our finding that IL-4 antagonizes IL-2-dependent growth of activated normal B cells is in line with the recent data obtained with chronic lymphocytic leukemia B cells (B-CLL), whose IL-2-dependent proliferation is totally blocked by IL-4 (45) .…”
Section: Discussionmentioning
confidence: 99%
“…Finally, IFN-␣ and IL-4 have opposing effects on hematopoiesis: IFN-␣ inhibits the proliferation of multipotent, granulocyte-macrophage, erythroid and megakaryocyte progenitor cells, whereas IL-4 acts in concert with other growth factors to promote the growth of multiple hematopoietic lineages [45][46][47][48][49][50][51][52][53][54][55][56]. However, IL-4 inhibits macrophage progenitor proliferation in vitro [55][56][57]. The reason that IFN-␣ and IL-4 share the ability to induce DC differentiation of monocytes is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…It may promote or suppress the maturation of haemopoietic cells, as progenitor cells respond differently to IL-4, at different stages of maturation (Rennick et al, 1987). Direct effects of inhibition or stimulation have been reported on melanoma cell lines (Mortarini et al, 1990).…”
mentioning
confidence: 99%